A critical exploration of surgical-oncology nurse’s perceptions of factors involved in decision making on postoperative wound management : a descriptive survey - Charalampous, Melanie; Charalambous, Andreas (My University, 2010)
Aim: To explore the Cypriots surgical-oncology nurse’s perceptions on postoperative wound management and to identify factors involved in decision-making on this topic. The risk factors that influence the quality of wound management were also explored. Methods and design: A survey design was employed in combination with semi-structured interviews that was undertaken between January-February 2009. A questionnaire was designed and distributed to all surgical nurses of seven surgical wards in a Cyprus Hospital (132 nurses). Seven nurses were randomly selected and interviewed.The completed questionnaires were coded and analyzed with the SPSS program.The interviews were transcribed verbatim and analyzed manually with the use of thematic analysis. Results: The absence of nurse’s up-to-date knowledge and the absence of wound care guidelines appear to negative influence the postoperative wound care decision-making. Furthermore, the influencing role of the doctors in deciding how to manage postoperative wounds is one of the factors that nurses identified as a negative influence to their autonomy. Workload was identified as a major factor that influences the quality of postoperative wound care and maximizes the occupational risks in nurse’s area of practice. The nurses have influences which hindered them to make decision on postoperative wound management and the findings are consistent with the relevant literature.The findings can become a useful tool for policy makers and hospital administrators in order to find ways to improve postoperative wound care decision-making.
Keywords: Nurses; Cancer--Nursing